Evaluasi tentang Pelaksanaan Tugas dan Tanggungjawab Polisi Kehutanan dalam Menanggulangi Illegal Logging - Indhasari, Fitri; Solihin (Pangale Journal of Forestry and Environment, 2022)
The current condition of Indonesia’s forests is very worrying with the increasing rate of forest degradation and illegal logging which is still common in Luwu Regency and the forestry police have the duty and responsibility and authority to protect the forest from illegal logging crimes. This study aims to determine the tasks and implementation of performance, obstacles and efforts made by the forest police in the context of monitoring, securing and protecting forest areas. This research was conducted from April to June 2021 at Luwu Regency Agriculture and Plantation Office. The method used in this research is sociological juridical which discusses the authority of the forest police and the application of criminal law in the effort to eradicate illegal logging. The results of the study indicate that the authority of the forest police is still in the investigation stage and has not yet been investigated, and efforts have been made with preventive and repressive approaches.